Exploring characteristics and common features of digital health in pediatric care in developing countries: a systematic review - Irawan, Anggi Septia; Döbrössy, Bence Márton; Biresaw, Mengesha Srahbzu; Muharram, Arief Purnama; Kovács, Szilárd Dávid; Girasek, Edmond (Frontiers in Digital Health, 2025)
BackgroundDigital health technologies have emerged as promising solutions to alleviate the scarcity of healthcare workers in developing countries. This systematic literature review aims to comprehensively explore the characteristics and common features of digital health interventions in pediatric care among parents and healthcare workers in these regions.MethodsA literature search was conducted on the PubMed and Scopus databases in January 2023, covering the period up to December 2022. The search adhered to the PRISMA guidelines. The PECOS format outlined by PROSPERO was used to determine the eligibility of systematic reviews and primary studies, with no restrictions on study designs or methodologies. Eligible articles comprised original research published in peer-reviewed open-access journals. The methodological quality of the included articles was independently assessed by authors using the CASP checklists to evaluate reporting quality.ResultThe initial search yielded 1,334 publications, of which 16 met the inclusion and exclusion criteria for the review. These comprised 12 random control trials and 4 Mixed methods studies. The CASP criteria were applied to all studies, and those with a moderate to high level of methodological quality were included and reported. The reviewed publications described various types of Digital Health tools, with a majority (50%) of the studies conducted in Asia. The target users in the publications were diverse, with 37% focusing on mothers, 25% targeting pregnant women, and 19% targeting healthcare workers.ConclusionsThe review highlighted a diverse range of tools, including mobile applications, websites, SMS, and phone calls, with a particular focus on breastfeeding, vaccination, and child growth. The findings emphasized the importance of healthcare worker participation, and the trust placed in information from relatives to influence the effectiveness of these tools. Moreover, the study underscored the need for intimate discussions when addressing sensitive topics like HIV. This review enhanced our understanding of the role of digital health tools in pediatric care in developing countries. It highlighted their potential to bridge healthcare gaps and promote wider access to quality care, addressing the challenges posed by limited healthcare resources in these regions. Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023383846, identifier: CRD42023383846.